Pitfall or Panacea: The Irony of U.S. Power in Occupied Japan, 1945-1952 - Yoneyuki Sugita (East Asia: History, Politics, Sociology and Culture, 2003)
The main purpose of this book is to shed light on the limitations of the American hegemony in occupied Japan. Previous studies share the assumption that the United States was in a near-monopoly position to shape the postwar development in Japan as well as in the Asia-Pacific region. The book goes on to modify the prevailing view that American hegemony not only eroded under its own weight, but was never absolute in any case. Japan, a former enemy, eventually became America's main regional ally in the Asia-Pacific region.